2020
DOI: 10.5267/j.msl.2020.3.023
|View full text |Cite
|
Sign up to set email alerts
|

Purchase intention on Indonesia male’s skin care by social media marketing effect towards brand image and brand trust

Abstract: This paper investigates the impact of social media marketing on brand image and brand trust toward the purchase intention of Indonesian Male's Skincare. The study proposes a model that shows the effect of skincare marketing strategies through social media for male millennials generations. A quantitative approach is used to collect the data to support the model using online surveys. The data samples are collected from 203 male respondents using non-probability sampling techniques with convenience sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
56
1
36

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 27 publications
19
56
1
36
Order By: Relevance
“…The f 2 effect size of the link between brand trust and purchase intention was small (0.066). The previous empirical studies confirmed the results of this research (Aydin et al, 2014;Sanny et al, 2020). Besides, the study results also pointed out that perceived value had a positive impact on brand preference.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The f 2 effect size of the link between brand trust and purchase intention was small (0.066). The previous empirical studies confirmed the results of this research (Aydin et al, 2014;Sanny et al, 2020). Besides, the study results also pointed out that perceived value had a positive impact on brand preference.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, there was an impact between brand trust and purchase intention, which indicates if brand trust has developed, then the rate of purchase intention will grow (Aydin et al, 2014;Sanny et al, 2020). Prior studies confirmed that brand trust had a positive effect on purchase intention (Aydin et al, 2014;Sanny et al, 2020). Therefore, we suggested the following hypotheses: H1: Brand trust has a positive effect on brand preference.…”
Section: Brand Trustmentioning
confidence: 90%
See 1 more Smart Citation
“…Young country and the internet-savvy population. Men consumer is increasingly on the radar of cosmetics companies all over the world, and in Indonesia this market segment is just a starting point [11].…”
Section: Figure 1 Ms Glow For Men Productsmentioning
confidence: 99%
“…Social media marketing has had a significant impact on brand image and brand trust. In addition, brand trust and brand image have had a significant impact on the purchase intention [11]. Factors that influence the behavior of the men consumer purchase of skin care products in Suwon, South Korea consisting of Normative Influences and Attitudes for Applying Skin Care.…”
Section: Introductionmentioning
confidence: 99%